Seismic Performance of the Inerter and Negative Stiffness–Based Dampers for Vibration Control of Structures - Islam, Naqeeb Ul; Jangid, R. S. (Frontiers in Built Environment, 2021)
Passive energy dissipation devices or supplemental damping devices have been successfully implemented into structures as seismic energy control devices. Recent developments in the form of negative stiffness dampers (NSDs) and inerter based vibration absorbers (IVA) as potential energy dissipation devices are widely studied. The present study evaluates the performance of negative stiffness and inerter based energy dissipation devices as possible alternatives to traditional energy dissipation devices like viscous dampers (VDs) and visco-elastic dampers (VEDs). The research focuses on the mathematical formulation and optimal design of novel negative stiffness and inerter based mechanisms. A 20-storey benchmark building is modelled as a multiple degree of freedom (MDOF) shear building. The dynamic equation equations for the MDOF system are written in state-space form, and a simple optimisation approach based on effective modal damping is prescribed. A comparative analytical analysis between traditionally applied and novel energy dissipation mechanisms, (i.e. IVA and NSDs) is studied. The study focuses on developing design considerations to analyse structures employing negative stiffness and inerter based energy dissipation devices. The study also shows that NSDs and IVA-based passive energy dissipation devices are the most efficient devices in reducing inter-storey drifts and floor accelerations compared with VDs and VEDs using the same damping coefficient.